Access to antiretroviral drugs in South Africa: the HIV/AIDS crisis in the light of the TRIPS Agreement, South African intellectual property and competition law - Voogd, Janina (Centre for Law and Society, 2026)
The HIV/ AIDS crisis has reached a high degree of prominence and awareness in both developed and developing countries. However, at the same time rural areas with no, little or very inaccurate knowledge of the HIV/AIDS problem can still be found all over the world. Furthermore, it seems that the awareness for the problem has had its peak a few years ago and that, since then, it has decreased at least on the international level. It somehow appears that the immense crisis is not seen as such nowadays and that people all over the world - but particularly in many third-world countries - have accommodated to its cruel results. The dimensions of HIV/ AIDS seem to be taken as some kind of bizarre normality in many countries. Furthermore, the developed world appears to have acknowledged the fact that developing countries and HIV/ AIDS present an inseparable phenomenon.